Intraductal Neoplasms of the Pancreas: An Update - BAĞCI ÇULÇİ, PELİN (FEDERATION TURKISH PATHOLOGY SOC, 2017)
With improvements in imaging to detect silent pancreatic lesions and increases in the number of centers now performing pancreatic surgery, more surgeries have been performed for indications other than invasive carcinoma. This has enormously added to our knowledge of the intraductal neoplasms of the pancreas. In addition, our understanding of the genetics of these lesions has expanded with the introduction of routine molecular genetic analyses. In this review, we provide an update into the most common intraductal neoplasms, namely intraductal papillary mucinous neoplasm and intraductal tubulopapillary neoplasm. We first focus on their clinicopathologic and molecular features of relevance to the practicing pathologist and then discuss their differential diagnoses.
Keywords: Pancreatic intraductal tumors; IPMN; ITPN; PAPILLARY-MUCINOUS NEOPLASMS; ACINAR-CELL-CARCINOMA; BRANCH DUCT-TYPE; INTERNATIONAL CONSENSUS GUIDELINES; OVARIAN-TYPE STROMA; CYSTIC NEOPLASMS; CLINICOPATHOLOGICAL FEATURES; DIFFERENTIAL-DIAGNOSIS; INVASIVE-CARCINOMA; ONCOCYTIC-TYPE